1993
DOI: 10.1017/s0025315400034809
|View full text |Cite
|
Sign up to set email alerts
|

Nassarius reticulatus (Nassariidae: Gastropoda) as an indicator of tributyltin pollution before and after TBT restrictions

Abstract: Between 1984 and 1993, levels of imposex (the induction of male characters including a penis on females) were measured in gastropods Nassarius (Hinia) reticulatus (L.) at localities in south-west England. Since tributyltin (TBT) was thought to cause imposex, concentrations in tissues and sea-water were also determined. Measurements made prior to the restriction of TBT usage in 1987 showed that intensities of imposex were related to TBT levels in females. Tissue concentrations were also related to those of sea-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 23 publications
7
48
1
2
Order By: Relevance
“…This was conclusively shown for Nucella lapillus (e.g. Bryan et al 1986) and also for Nassarius reticulatus after both field (Stroben et al 1992b, Bryan et al 1993, Huet et al 1995, Barreiro et al 2001, Barroso et al 2002a) and laboratory (Stroben et al 1992a, Bettin et al 1996, Barroso et al 2002b studies. The present work adds to this database with a regional survey, where the relationship between RPLI and TBT (Fig.…”
Section: Biological Effectsmentioning
confidence: 53%
See 3 more Smart Citations
“…This was conclusively shown for Nucella lapillus (e.g. Bryan et al 1986) and also for Nassarius reticulatus after both field (Stroben et al 1992b, Bryan et al 1993, Huet et al 1995, Barreiro et al 2001, Barroso et al 2002a) and laboratory (Stroben et al 1992a, Bettin et al 1996, Barroso et al 2002b studies. The present work adds to this database with a regional survey, where the relationship between RPLI and TBT (Fig.…”
Section: Biological Effectsmentioning
confidence: 53%
“…2) is similar to that described in those previous reports. For instance, both Bryan et al (1993) (data for pre-restriction years 1985-87) and Barroso et al (2002a) also found a sharp RPLI increase for TBT up to around 200 ppb Sn DW. At higher concentrations, however, while data in Barroso et al (2002a) tended to a plateau at approximately 85% for TBT up to 1400 ppb Sn DW, the few pre-restriction data in Bryan et al (1993) suggest a positive slope up to 500 ppb Sn DW, which is now confirmed to be significant over an even wider TBT range.…”
Section: Biological Effectsmentioning
confidence: 94%
See 2 more Smart Citations
“…On the contrary, N. lapillus accumulates TBT preferentially via water and food (mainly mussels and barnacles which, by their turn, accumulate TBT from the water column) and so the levels of imposex in the dog-whelk predominantly indicates the level of pollution in the water. 15,36,37 Similarly to H. ulvae, N. reticulatus is a sediment-dweller, adults feed on carrion and do not ingest substrate particles. This nassarid is a scavenger 38 in which food was described as contributing more than half of the TBT body burden, 36 minimizing the effect of the direct uptake by the contact with its internal/external body surface.…”
Section: Stmentioning
confidence: 99%